The Mediating Role of Employee Engagement in the Relationship between Perceived Organizational Support and Motivation with Employee Performance - Risma Kencanamurti; Tristiana Rijanti (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to investigate the effect perceived organizational support and motivation toward employee engagement. A further objective is to analysis the role of perceived organizational support, work motivation, and employee engagement in driving employee performance. This research design adopted a quantitative survey approach. The study sample consisted of all 107 employees of the Transportation Agency in Pati Regency, Central Java, selected using a census technique. The collected data were analyzed using descriptive statistics, validity test, reliability tests, and multiple linear regressions. The mediation role was analyzed using the Sobel test. The initial research findings indicate that organizational support and motivation have a positive impact on employee engagement. Further study findings indicate that perceived organizational support, motivation, and employee engagement have a significant effect on employee performance. The research findings contribute theoretically to the field of human resources by demonstrating the employee engagement as intervening variable in the relationship between perceived organizational support and motivation toward employee performance.